Determination of the deformation of a rigid seeding surface under shock and vibration action - Zaselskyi , V.Y.; Popolov , D.V. (Theory and Practice of Metallurgy, 2024)
For screening mining and metallurgical raw materials, especially in conditions where clogging of the screen holes can significantly reduce the process performance, an urgent task is the need to improve the efficiency of classification. The aim of this work is to determine the deformation of a rigid screening surface under the influence of shock and vibration. In this work, a calculation scheme and an algorithm for determining the deformation of the sieve. The sieving surface was represented as a system of elementary beam strips that undergo deformation in both the longitudinal and and transverse directions under the influence of shock and vibration. Elasticity theory was used to analyze the deformations, as well as numerical modeling to calculate the stiffness of the sieve and determine its deformation characteristics. The results of the study showed that the deformation of the sieve depends on vibration angles and relative elongation of the sieving surface elements. It was found that at small relative elongations (up to 0.001), the displacement of the of the deflection boom in the longitudinal direction is insignificant and does not affect sieve performance. Significant deformations that may affect its operation occur only at large relative elongations, which are unacceptable in production conditions. The developed calculation scheme allows for a more accurate assessment of the deformation properties of the sieve and can be used to optimize its design. The proposed methods can be implemented in production processes, which will optimize the processes, which will optimize the operation of technological units and reduce the cost of their operation.